Asessing Adherence to the Use and Remove of peripheral intravenous (IV) catheter amongst nurses at An Giang Center General Hospital in 2021 (Vietnam Journal of Community Medicine, 2022)
Objective: This study assesses investigate the incidence of adherence of nurses and its association with the Use and Remove of peripheral intravenous (IV) catheter in hospitalized adults at An Giang Center General Hospital in Vietnam in 2021.Methods: This cross-sectional study (quantitative method) was conducted within 2 months (April-June/2021) at An Giang Center General Hospital. Quantitative data was collected by observation checklist for all 152 nurses during their Use of peripheral IV catheter and following catheter removal. Data was analyzed using SPSS ver 25.0.Findings: The rate of adherence to the use of peripheral IV catheter of nurses was 54.0%, of which the highest rate was 76% of the nurses in the Internal Medicine Department and the lowest rate was 42% of the nurses in the Emergency Department and the Intensive Care Department. Regarding the removal of peripheral IV catheter of nurses, the rate of adherence of nurses was 68.4%. In which, the highest rate was 79.6% of the nurses in the Internal Medicine Department and 58.0% of the nurses in the the Emergency Department and the Intensive Care Department.Conclusions: An Giang Center General Hospital needs to promote communication, training, monitoring and evaluation for nurses to properly adhrere to the use of peripheral IV catheters (PIC) and following their removal.
Keywords: Peripheral intravenous (IV) catheter, nurses, An Giang Center General Hospital.